EU agricultural policy and productivity of soil in countries varying in terms of farming intensity = Polityka rolna UE a produktywność ziemi w krajach różniących się intensywnością rolnictwa - Smędzik-Ambroży, Katarzyna; Majchrzak, Adam (Zielona Góra: Faculty of Economics and Management Press)
It was emphasised in the work whether there are differences in soil productivity of FADM farms from countries belonging to EU-15 and EU-12, and whether CAP subsidies impact the degree of these differences. For this purpose, a comparative analysis was conducted for the soil productivity indicators (taking into account the value of CAP subsidies in the value of production from agricultural activity and without such subsidies) as well as a statistical assessment of differences between those indicators in EU-15 and EU-12 countries based on the Mann?Whitney U test. EU-FADN data was used in the work.
Keywords: produktywność ziemi; intensywność rolnictwa; polityka rolna UE; UE-15; UE-12; soil productivity; agricultural intensity; EU agricultural policy